People are really the most important resource of organizations? An analysis of the scientific production on quality of working life (QWL) - Venson, Aline Botelho Schneider; Fiates, Gabriela Gonçalves Silveira; Dutra, Ademar; Carneiro, Marcelo Lopes; Martins, Cristina (Revista de Administração da UFSM, 2013)
DOI: 10.5902/198346595705 The discourse in organizations in general, regardless of size or nature, focuses on a recurring basis the relevance of human capital for success and direct relationship between employee performance and organizational results. Studies about quality of work life are extremely important to understand the variables that impact performance and results for both: the organization and its employees. To evaluate how scientific research reflect this importance, this study has been developed to analyze the scientific production on the subject of quality of work life - QWL in Brazil, analyzing the articles published in the annals of EnANPAD - Meeting of the National Association Postgraduate and Research in Administration. This is a bibliometric research of academic production in the period 1997 to 2011. After collection of information were found 64 articles that met at least one of keywords defined by the scope of this study. As a result it was found that the subject of quality of working life until 2008 was still discussed in scientific literature only incidentally, with an investigative nature, in order to diagnose only QVT index, without seeking to identify its impact on the organization as a whole. However, from 2009 it can already notice a maturity based on the identification of works that investigated the relationship between QWL, social responsibility, organizational commitment and, including, performance.